Electro-Magnetism in Battery Pot Plants with Heating Chambers for Heat Energy Transduction - Lena J-T Strömberg (ASEAN Journal of Science and Engineering, 2023)
Electro-magnetism for components and pot plants in interaction are studied with experiments and analysis. Experiments were done using a chamber for heat energy transduction in arrangements with battery electrodes in a pot. The process required heat to produce current and electric power together with the battery. This study also considered the performance in terms of more current and voltage. The largest device produced 0.16 mW. The function of the chamber is considered chamber amplification. This study also analyzed with Hamiltonian mechanics. An application outdoor was also presented to replace and understand the summer energy sources with electricity. By using this procedure, this study found that if a plant adapts, it develops durability of cold outside